Development of framework for Malay Reserved Land in Malaysia - Ishak, Mohammad Firdaus; Nawawi, Abdul Hadi; Aliasak, Mohd Hasrol Haffiz; Zulkarnain, Siti Hafsah; Hashim, Siti Fatimah Hashim (UiTM Press, 2025)
Prominent concerns over the regulations governing Malay Reserved Land (MRL) in Malaysia are extensively debated among real estate stakeholders in the country. Concerns include inadequate information regarding the true extent of MRL in Malaysia, errors by inexperienced vendors in providing MRL information, clandestine transactions between owners and nonMalays, and the indefeasibility of title within the Malaysian property system. These concerns necessitated an intervention to enhance the MRL's system. This study seeks to establish a successor framework for the MRL in Klang Valley, Selangor. To accomplish this objective, two (2) methodologies are employed: Secondary Data Analysis and Primary Data Collection and Analysis. In Primary Data Collection and Analysis, the quantitative method is chosen as the primary data collection approach, while the qualitative method is utilised for framework validation. This framework aims to elucidate the new MRL system and will assist Malaysian local authorities with MRL-related concerns.